Germinación De Semillas De Asclepias Subulata En Condiciones De Casa Sombra Utilizando Ácido Giberélico - López-Elías, Jesús; Jiménez-León, José; Huez-López, Marco A.; Dávila-Loreto, Jesús A.; Ávila-Machado, Efraín; Robles-Zepeda, Ramón E. (European Scientific Journal, ESJ, 2017)
The objective of this work was to evaluate the use of gibberellic acid (GA3) in the seed germination of Asclepias subulata Decne., plant of the wild flora of the Sonoran Desert of interest for reforestation, industry and medicinal use. Since there is no information about their domestication, it is of fundamental importance to carry out germination tests to ensure their propagation, given the low germination percentage that this species presents. Seeds of A. subulata were collected in the Sonoran Desert, within the area known as Cerro del Bachoco. Six concentrations of gibberellic acid (GA3) (0, 125, 250, 500, 1000 and 2000 ppm) were tested at two soak times (24 and 48 hours) and one control without any treatment. Germination power, germination time at 25, 50 and 75%, and the germination rate index were evaluated. Germination was considered when the seed emits the hypocotyl outside the substrate used. Chemical scarification with GA3 has a positive influence on seed germination of A. subulata. The highest percentage of germination was obtained with GA3 in concentrations of 250 to 2000 ppm, at 24 and 48 hours of soaking. Germination time was affected by the concentration of GA3, being favored at a concentration of 1000 and 2000 ppm at 24 and 48 hours of soaking; while in other treatments 75% of germination was not reached. Chemical scarification with GA3 favored the germination rate index.